OPTIMALISASI KOMPETENSI PEDAGOGIK GURU SD MELALUI PEMBELAJARAN BERDIFERENSIASI BERBASIS ETHNO-RME - Junaedi, Yusup; Mukhoyyaroh, Qiswatun; Anwar, Syahrul (LPPM Universitas Sangga Buana, 2024)
This community service is motivated by the importance of differentiated learning to facilitate students' learning needs, in addition to the need to use teaching materials that are close to students' daily lives through an approach based on Ethno-Realistic Mathematics Education. The purpose of this activity is to optimize the pedagogical and professional skills of elementary school teachers through training and mentoring in digital differentiated learning based on Ethno-Realistic Mathematics Education. This activity was carried out at SD Negeri Tunjung 1 involving 38 elementary school teachers who are members of the Teacher Working Group (KKG) Gugus 1 Korwil Kec. Tunjung Teja. Mentoring and training were carried out by three lecturers from La Tansa Mashiro University with presentations of materials related to differentiated learning, Ethno-RME materials and sharing good practices of differentiated learning based on Ethno-Realistic Mathematics Education. The activity procedure consists of observation and interviews with partner schools, training and mentoring in preparing learning designs, developing differentiated learning and implementing Ethno-RME. The results of this service were an increase of 59,6% in the pedagogical and professional competence of teachers in digital differentiated learning based on Ethno-Realistic Mathematics Education.